Encephalitis in multisystem inflammatory syndrome in children (MIS-C) associated with SARS-CoV-2 infection: A case series - Bernardo, Luca; Brambilla, Marta; Sartorio, Marco Ugo; Sandini, Martina; Casini, Francesca; Di Mari, Clelia; Mauro, Angela (Acta Biomedica Atenei Parmensis, 2025)
Backgroung and aim: Multisystem inflammatory syndrome in children (MIS-C) associated with SARS-CoV2 infection is a systemic hyper-inflammatory condition affecting children with a recent acute SARS-CoV2 infection. It is usually characterized by persistent fever, mucocutaneous involvement, lymphadenopathy, gastrointestinal symptoms, cardiac dysfunction. Neurological involvement in MIS-C is frequent but not clearly defined: patients may develop acute neurological involvement, characterized by rapid onset of focal neurological signs and electrical abnormalities.Methods and results: Herein we report 3 cases of  children with MIS-C developing an acute encephalopathy.Conclusion: Additional data are needed in order to evaluate the prevalence of acute encephalitis in patients with MIS-C and characterize its presentation and define long-term outcomes.